PENYUTRADARAAN FILM DOKUMENTER GAYA ASSOCIATION PICTURE STORY ETANAN - Riandhani Yudha Pamungkas; Muhammad Zamroni; Soekma Yeni Astuti (Program Studi Film dan Televisi Universitas Jember, 2018)
There are so many natural resources in Tapal Kuda region. Meanwhile,Tapal Kuda also have ethnic, cultural and religious diversity, and good industrial growth in each regency. However, the education infratstructure is uneven, so there are still many areas left behind with high illiteracy rates. Documentary film with Association Style Picture Story is an alternative commentation of Tapal Kuda region. This Documentary film use Lacan’s Psychoanalis analogy which is created the phase of human development. ETANAN as an effort to deconstruct the ability of numbers that already exists. Association Picture Story style combined the numerical data and all the facts which is created a brand new view point and perspective for the audiences. ETANAN film illustrates the condition of natural resources, etnics, culture and the educations with association in Tapal Kuda region and creates the new perspective and meanings in a Association Picture Story style.